Digital journalism after mobility - Goggin, Gerard (2022)
This article provides a commentary on the special issue of ‘Digital Journalism’ on news, mobiles, and mobilities. It reviews and discusses the articles in relation to news, journalism, and mobile media trends. It suggests four key areas for the future research agenda: deepening internationalization of empirical and theoretical work; mobiles as key to larger trends and systems in digital media and journalism; cross-app, platform, and technology comparative work; reimagining journalism education and media work and professions, to reflect the deep changes at work in mobile news and mobilities of news and digital journalism.